A simple maneuver to determine if septal accessory pathway ablation requires a left atrial approach. (24th September 2020) - Kanawati, Juliana; Roberts, Jason D.; Rowe, Matthew K.; Khan, Habib; Chan, William K.; Leong‐Sit, Peter; Manlucu, Jaimie; Yee, Raymond; Tang, Anthony S.; Gula, Lorne J.; Skanes, Allan C.; Klein, George J.
Abstract: Introduction: Septal accessory pathway (AP) ablation can be challenging due to the complex anatomy of the septal region. The decision to access the left atrium (LA) is often made after failure of ablation from the right. We sought to establish whether the difference between ventriculo‐atrial (VA) time during right ventricular (RV) apical pacing versus the VA during tachycardia would help establish the successful site for ablation of septal APs. Methods: Intracardiac electrograms of patients with orthodromic reciprocating tachycardia (ORT) using a septal AP with successful catheter ablation were reviewed. The ∆VA was the difference between the VA interval during RV apical pacing and the VA interval during ORT. The difference in the VA interval during right ventricular entrainment and ORT (StimA–VA) was also measured. Results: The median ∆VA time was significantly less in patients with a septal AP ablated on the right side compared with patients with a septal AP ablated on the left side (12 ± 19 vs. 56 ± 10 ms, p  < .001). The StimA–VA was significantly different between the two groups (22 ± 14 vs. 53 ± 9 ms, p  < .001). The ∆VA and StimA–VA were always ≤ 40 ms in patients with non‐decremental septal APs ablated from the right side and always greater than 40 ms in those with septal APs ablated from the left. Conclusion: ΔVA and StimA–VA values identified with RV apical pacing in the setting of ORT involving a septal AP predict when left atrial access will be necessary for successful ablation.